PENGELOLAAN PRODUK ECOENZIM UNTUK PENINGKATAN KESADARAN MENJAGA LINGKUNGAN PADA PONPES AL MISBAH BOGOR - Handayani, Tati; Matondang, Nurhafifah; Mulyantini, Sri; Sumilir, Sumilir; Amalia, Farida; Salim, Abdurrahim (Jurnal Abdimas Bina Bangsa, 2024)
Pesantren is a traditional educational institution rooted in Islam, which focuses on the study and application of Islamic religious practices as the core of its education. As times evolve, Islamic boarding schools must develop innovation by integrating the general education curriculum into the Islamic boarding school curriculum. The aim is that the students not only have religious knowledge, but also gain general knowledge to compete with graduates from different educational backgrounds. This applies both in the context of everyday life and in the academic realm. Eco enzyme or environmentally friendly enzyme is made from residue or household waste such as vegetable waste, fruit peels and other household waste. This enzyme has commercial value if processed with the right knowledge. Therefore, the main aim of this community service activity is to provide knowledge and provide training on eco enzyme processing to encourage the entrepreneurial spirit and skills of Islamic boarding school members. This community service also has a questionnaire and provides positive feedback for Al Misbah boarding school students. The results of this activity are a real contribution in making independent and empowering Islamic boarding school students through the implementation of ecoenzymes by producing soap products